Distribution, ecological tolerance and optimum levels of freshwater Ostracoda (Crustacea) from Diyarbakir, Turkey - (:unkn) unknown (SPRINGER JAPAN KK, 2012)
A total of 23 ostracod taxa were found in 48 of 90 different water bodies (wetlands, springs, lakes, creeks, etc.) located at moderate to high elevation (530-1,095 m) in DiyarbakA +/- r province. The ecological tolerances and optimum values for environmental variables of 15 species were analyzed. Accordingly, maximum numbers of species were found between 700 and 800 m. Ostracod species and sampling sites along with seven environmental variables were ordinated with canonical correspondence analysis (CCA). The first axis of CCA explained 72% of the relationship between species and environmental variables. Of these, water temperature, redox potential and altitude were the most influential (P < 0.05) factors for species. Based on habitat similarities, an unweighted pair group mean average dendrogram divided species into four clustering groups. Among the species, Potamocypris arcuata, Candona neglecta and Psychrodromus fontinalis had the highest optimum estimates for altitude, whereas P. arcuata, Herpetocypris brevicaudata and P. fontinalis exhibited the highest tolerances to altitude. While most species revealed unique tolerances and optimum values for different ecological variables, species with cosmopolitan characteristics had wider ranges of ecological tolerances and distribution amid the variety of habitats along elevational gradients.
Keywords: Ostracoda; Cosmopolitan; Distribution; Habitat preferences; Ecology; BOLU; LAKE; REQUIREMENTS; PATTERNS; SPRINGS; ALTITUDE; REGIONS